2001
DOI: 10.1093/bioinformatics/17.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Multi-class protein fold recognition using support vector machines and neural networks

Abstract: Most current discriminative methods for protein fold prediction use the one-against-others method, which has the well-known 'False Positives' problem. We investigated two new methods: the unique one-against-others and the all-against-all methods. Both improve prediction accuracy by 14-110% on a dataset containing 27 SCOP folds. We used the Support Vector Machine (SVM) and the Neural Network (NN) learning methods as base classifiers. SVMs converges fast and leads to high accuracy. When scores of multiple parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
650
0
21

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 750 publications
(682 citation statements)
references
References 20 publications
11
650
0
21
Order By: Relevance
“…The fold database used in our experiments is derived from the work of (Ding and Dubchak, 2001). It contains a training set and a testing set that contain 313 and 385 proteins.…”
Section: Protein Fold Recognition (Fold)mentioning
confidence: 99%
See 3 more Smart Citations
“…The fold database used in our experiments is derived from the work of (Ding and Dubchak, 2001). It contains a training set and a testing set that contain 313 and 385 proteins.…”
Section: Protein Fold Recognition (Fold)mentioning
confidence: 99%
“…In order to validate the effectiveness of the presented method, we compare it with several methods in different literatures all of which used the same benchmark data sets and the same testing protocol of original paper (Ding & Dubchak, 2001), it is the dataset named FOLD in this work. The comparison is listed in Table 4.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research, however, has suggested that the SVM is superior to the neural network (13)(14)(15). To verify this, and to test our method, we used a multilayer propagation (MLP) neural network model, as well as an SVM, to classify tumors in our experiments.…”
mentioning
confidence: 99%